2013
DOI: 10.1186/1746-6148-9-53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lateral meniscectomy and osteochondral grafting of a lateral femoral condylar defect on contact mechanics: a cadaveric study in dogs

Abstract: BackgroundOsteochondral autograft transfer (OAT) aims at restoring normal articular cartilage surface geometry and articular contact mechanics. To date, no studies have evaluated the contact mechanics of the canine stifle following OAT. Additionally, there are no studies that evaluated the role of the meniscus in contact mechanics following OAT in human or canine femorotibial joints. The objective of this study was to measure the changes in femorotibial contact areas (CA), mean contact pressure (MCP) and peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The use of hinge plates has also proven to be reliable in earlier studies. 11,15,22 The I-Scan system was previously successfully used in other studies 15,[23][24][25][26][27] . Their research group was able to show impressively how femorotibial contact mechanics change after meniscal surgery or damage and how TPLO and other techniques influence stifle kinetics and kinematics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of hinge plates has also proven to be reliable in earlier studies. 11,15,22 The I-Scan system was previously successfully used in other studies 15,[23][24][25][26][27] . Their research group was able to show impressively how femorotibial contact mechanics change after meniscal surgery or damage and how TPLO and other techniques influence stifle kinetics and kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Their research group was able to show impressively how femorotibial contact mechanics change after meniscal surgery or damage and how TPLO and other techniques influence stifle kinetics and kinematics. 15,[23][24][25][26]28 Nevertheless, the influence of postoperative TPA on the meniscal load was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, injury to the lateral meniscus is rare by comparison with injury to the medial meniscus, and the cause of the injury can be cruciate ligament degeneration and stifle instability, stifle trauma associated with ligament injury,1 as an isolated injury,2 8 9 or in association with osteochondrosis dissecans 10. Studies in dogs have shown that, as in human knee, the lateral meniscus is more important in load transmission across the lateral femorotibial joint space than the medial meniscus 11. Therefore, significant damage to or complete loss of the lateral meniscus could be expected to lead to significant joint degeneration and pain through loss of its function,2 and small, incomplete, radial fringe tears may not have a significant impact on joint health 1.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies in dogs have shown that, as in human knee, the lateral meniscus is more important in load transmission across the lateral femorotibial joint space than the medial meniscus. 11 Therefore, significant damage to or complete loss of the lateral meniscus could be expected to lead to significant joint degeneration and pain through loss of its function, 2 and small, incomplete, radial fringe tears may not have a significant impact on joint health. 1 In the case described the initial diagnostic arthroscopy revealed such extensive damage to the lateral meniscus that the authors considered the prognosis for a good functional outcome with total lateral meniscectomy to be poor.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs are better models for cartilage defects, as the thicker cartilage thickness of dogs allows creation of full or partial defects of articular cartilage without involvement of subchondral bone [9,69]. A majority of studies still utilize the osteochondral defect model in dogs [70,71]. Dog cartilage defects were selectively created in the femoral trochlea, the medial femoral condyle, and both condyles.…”
Section: Anatomymentioning
confidence: 99%